2010
DOI: 10.1097/mph.0b013e3181c97c57
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Papillary Carcinoma in a 3-year-old American Boy with a Family History of Thyroid Cancer

Abstract: Differentiated thyroid carcinoma is a rare malignancy in children. It represents 0.4% to 3.0% of all childhood malignancies, with greater than 70% of cases presenting between the ages of 11 to 17 years and is exceptionally rare in children under 5 years of age. The most common type of differentiated thyroid carcinoma in children is papillary thyroid carcinoma, most of which are believed to be related to radiation exposure and only approximately 5% of cases have a family history of papillary thyroid cancer. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Until reliable genetic testing becomes available, obtaining a detailed family history is of great importance for recognition of any familial link to FPTC. Recently, Khara et al reported a 3-year-old boy with familial PTC [ 16 ]. Since the patients in the second generation are frequently younger than the first generation counterparts, preoperative screening should be conducted at the age of 18 years according to expert consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Until reliable genetic testing becomes available, obtaining a detailed family history is of great importance for recognition of any familial link to FPTC. Recently, Khara et al reported a 3-year-old boy with familial PTC [ 16 ]. Since the patients in the second generation are frequently younger than the first generation counterparts, preoperative screening should be conducted at the age of 18 years according to expert consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients were frequently younger in the second generation as compared to first generation, screening should start at the age of 18 years. Recently, Khara et al reported a 3-year-old boy with familial PTC [30]. As soon as suspicious lesions are detected by ultrasound, total thyroidectomy seems to be the procedure of choice with regard to an often multifocal tumor growth of FNMTC.…”
Section: Recommendations For Treatment and Screening Of Fnmtcmentioning
confidence: 98%
“…The fPTC occurs most commonly, but it has also been described in other types of well-differentiated thyroid carcinoma (Ito et al, 2008). Khara et al (2010) described the appearance of fPTC in the case of a 3-year-old boy. Although the genes involved in the inheritance of the familial form of medullary thyroid carcinoma have been identified, the hereditary patterns of the fPTC are still unknown.…”
Section: Discussionmentioning
confidence: 99%